Perancangan Sistem Informasi Operating Time Mesin Secara Real Time - Priyo Ari Wibowo; Albertus Tomi (Operations Excellence: Journal of Applied Industrial Engineering, 2021)
Information technology in this era has an influence and provides convenience in the production process, data processing and information delivery. In addition, the performance of machines or equipment is also more guaranteed in terms of data accuracy in operation. The purpose of this research is to design and build an information system in the production line related to operating time and downtime information, so that machine performance can be controlled quickly and can be evaluated on the spot (real time). The speed of this information will make it easier to make decisions or change strategies quickly. Downtime is the main source that causes lost productivity so that with faster handling of downtime, companies can get significant production results.